2013
DOI: 10.1016/j.ijscr.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Primary angiosarcoma of breast: A case report

Abstract: Primary angiosarcoma of the breast is a rare malignancy with a poor prognosis, even after complete resection. Surgery is the mainstay of treatment with a limited role for chemotherapy and radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 15 publications
0
42
0
1
Order By: Relevance
“…Some patients are diagnosed during pregnancy or shortly after delivery (7); it is believed that there is a hormonal effect on the development of this disease. However, there are several cases of bilateral tumors diagnosed in postmenopausal period (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients are diagnosed during pregnancy or shortly after delivery (7); it is believed that there is a hormonal effect on the development of this disease. However, there are several cases of bilateral tumors diagnosed in postmenopausal period (8).…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, the tumor may show a soap bubble appearance. They rarely manifest coarse, nonbranching microcalcifications (8). PBA could be seen as having focal asymmetry, an oval or lobular mass feature, and rarely there may be skin thickening (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Há poucos relatos na literatura a respeito dos achados de imagem do angiossarcoma de mama na RM 7,11 . A apresentação mais comum é de um nódulo heterogêneo com baixa intensidade de sinal nas imagens ponderadas em T1 e alta intensidade de sinal nas imagens ponderadas em T2, com áreas de ausência de sinal em razão de vasos no interior da lesão 5,7,9,11,12 . A presença de cinética do tipo washout e de áreas de hemorragia favorecem tumores de alto grau 6,13 .…”
Section: Relato Do Casounclassified
“…In addition, the role of adjuvant chemotherapy and/or RT has also been elucidated, which suggested that patients with high risk of recurrence might benefit from adjuvant therapy. 10 , 11…”
Section: Introductionmentioning
confidence: 99%